Chromium and Cadmium Assessment in Selected Rice Varieties Under Various Irrigation Sources - Mehwish Aslam; Zafar Iqbal; Kafeel Ahmad; Faiza Zubair; Naila Riaz; Asma Ashfaq; Ijaz Rasool Noorka; Muhammad Irfan Ashraf; Saif Ullah (RADS Journal of Biological Research & Applied Science)
Background: Toxic metal accumulation in food crops poses significant public health risks. In particular, chromium (Cr) and cadmium (Cd) contamination in rice crops can lead to human exposure through dietary intake, emphasizing the need for ongoing monitoring and assessment.